2022
DOI: 10.1155/2022/6833196
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Acupuncture Combined with Exercise on Expression of Immune Factors in Aging Rats and Its Significance in Antiaging Intervention

Abstract: Background. With the improvement of people’s living standards, how to maintain health and delay aging to improve the quality of life and achieve longevity has become a hot topic of concern. objective. To investigate the effect of acupuncture combined with exercise on the expression of immune factors in aging rats and its significance in antiaging intervention. Materials and Methods. Forty-three SD rats included 12 rats in the control group, and the remaining rats were injected intraperitoneally with D-galactos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%